2011
DOI: 10.1007/s00266-011-9779-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Degeneration 7 Years After Breast Augmentation With Injected Polyacrylamide Hydrogel (PAAG)

Abstract: Injectable polyacrylamide hydrogel (PAAG) is a jelly-like transparent implant used in breast augmentations. This type of implant had been used since 1998, but its use was prohibited in China in 2006 due to numerous complications that had arisen from its use. In one case, a rare appearance of PAAG tissue degeneration was observed 7 years after an injectable breast augmentation using PAAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Previous histopathological findings of PAAG capsules revealed fibrous connective tissue hyperplasia, degeneration of breast tissue, formation of fibrous tissue, and fiber contraction, leading to displaced papillae and mastodynia [12]. Another report revealed macrophages and giant cells surrounding the PAAG, suggesting a foreign body reaction, similar to our finding [13].…”
Section: Discussionsupporting
confidence: 88%
“…Previous histopathological findings of PAAG capsules revealed fibrous connective tissue hyperplasia, degeneration of breast tissue, formation of fibrous tissue, and fiber contraction, leading to displaced papillae and mastodynia [12]. Another report revealed macrophages and giant cells surrounding the PAAG, suggesting a foreign body reaction, similar to our finding [13].…”
Section: Discussionsupporting
confidence: 88%
“…Third, the temporal pain could have been due to two causes. The first is the degeneration of the temporalis muscle after PAAG injection, which is supported by the previous observation of pectoral muscle degeneration induced by PAAG injected into the breasts [ 7 , 8 ]. Although we did not collect temporalis tissue for histological examination due to our concern that this might injure the facial nerves, the more severe pain in the left temple, where the muscles showed the most filler infiltration, and the pain induced by changes in facial expression may indicate muscle degeneration.…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown that polyacrylamide is harmless to the body, but the acrylamide monomer released from polyacrylamide contains toxins [ 17 ]. The toxicity of acrylamide mainly includes neurotoxicity, reproductive toxicity, genetic toxicity, immunotoxicity, and potential carcinogenicity [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%